Sposoby wizualizacji drzew klasyfikacyjnych i regresyjnych CART - Łapczyński, Mariusz (Ways of Visualizing CART Models, 2009)
The goal of this article is to show different manners of visualizing classification and regression trees built with CART algorithm. In addition to final outcome tree structure - the author demonstrates tree maps, diagrams of predicted and actual values, exploration of terminal nodes, partition of a tree, graphs of residuals and graphs of step function. The list of presented software includes CART(r), STATISTICA, DTREG, KLIMT, XLMiner, SYSTAT and R (package tree).
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s. 55-64